Womens role and position in the Yarsan religion - زریان جیزنی محەمەد (QALAAI ZANIST JOURNAL, 2019)
(Kakayi) Yarsan is an ancient Kurdish Religion; it is based on the other old religions in Kurdistan such as Metrayi and Zardashti. (Saranjam) is the holy book of Yarsan Religion. Yarsan is considered as part of Kurdish national heritage and has its own particular secular ceremonies; it could continuously develop and renew itself. In this thesis , we try to throw light on women class in the aspect of writing, music and religious education in Yarsan Religion along history, To enrich this subject more, we have referred to the well-known cultured women mentioned in the holy book (Saranjam) ; those women held high position in community and whose poems were interpreted and played their role side by side with men to serve and circulate the message of Yarsan Religion and educating the people.